Bureaucrats and bleeding hearts : indigenous health in northern Australia - Lea, Tess (UNSW Press, 2008)
Bureaucrats and Bleeding Hearts takes you on an intimate journey into the lives of people armed with the task of ending Australian Aboriginal disadvantage in the frontier north of Australia. Taking a fresh look at longstanding issues, Lea examines the culture of bureaucracy, its need to create the look of action, how intelligent inhabitants uphold the apparatus of government even whilst they critique it, and how benevolent efforts to improve health have brought about unexpected co-dependencies and tragic failures. She paints a sympathetic yet discomforting portrait of those who, working on behalf of and for Aboriginal health, fiercely defend the ideas and principles that paradoxically reinstate the primary need for greater levels of government intervention.